2021
DOI: 10.3390/catal11040486
|View full text |Cite
|
Sign up to set email alerts
|

Changes in CO2 Adsorption Affinity Related to Ni Doping in FeS Surfaces: A DFT-D3 Study

Abstract: Metal sulphides constitute cheap, naturally abundant, and environmentally friendly materials for energy storage applications and chemistry. In particular, iron (II) monosulphide (FeS, mackinawite) is a material of relevance in theories of the origin of life and for heterogenous catalytic applications in the conversion of carbon dioxide (CO2) towards small organic molecules. In natural mackinawite, Fe is often substituted by other metals, however, little is known about how such substitutions alter the chemical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
0
0
Order By: Relevance
“…Therefore, based on the results presented in this study, it can be concluded that the reactivity of Fe atoms around the S vacancy is significantly higher compared to those on the perfect pyrite surface. Živković et al [22] studied the adsorption behaviors of the CO 2 molecule on the FeS (011) surface-terminated Fe atoms and also found the Fe-O and Fe-C bonds. The difference in Fe atoms between the pyrite surface and the FeS surface is the amount of coordination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, based on the results presented in this study, it can be concluded that the reactivity of Fe atoms around the S vacancy is significantly higher compared to those on the perfect pyrite surface. Živković et al [22] studied the adsorption behaviors of the CO 2 molecule on the FeS (011) surface-terminated Fe atoms and also found the Fe-O and Fe-C bonds. The difference in Fe atoms between the pyrite surface and the FeS surface is the amount of coordination.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have extensively investigated the adsorption of CO 2 on various metal oxide [34,35] and sulfide surfaces [22,36]. For instance, Khaledialidusti et al [36] studied the adsorption behavior of CO 2 on the chalcopyrite (110) surface and reported both molecular and dissociative adsorption.…”
Section: Co 2 Molecule Adsorbed On Pyrite Surfacementioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, AIMD and DFT are used to study for instance relative stabilities (Li et al, 2009), adsorption behavior (Zivković et al, 2021), and crystal defects (Živković and De Leeuw, 2020). In the need to study larger-scale problems where AIMD methods fall short, atomistic force fields are generally a suitable alternative.…”
Section: Crystallization Theory In a Nutshellmentioning
confidence: 99%